Development of Assessment Instruments for Higher Order Thinking Skills (HOTS) on Ecosystem Material - Yenny Nurmawaddah; Agil Al Idrus; Kusmiyati Kusmiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
eval___uation of learning in secondary schools is still dominated by test items that only measure memorization skills, thus failing to encourage students’ Higher Order Thinking Skills (HOTS), as evidenced by research findings showing that students’ achievement in the ecosystem topic remains relatively low, with 65% of 30 students failing to reach the minimum mastery criteria (KKM). This study aims to develop and eval___uate the feasibility of HOTS assessment instruments based on expert validation and empirical testing. The study used a Research and Development (R&D) approach using the Plomp model, involving 115 Grade X students from two senior high schools in Labuapi District. The expert validation results indicated an instrument feasibility level of 86.39%, which falls into the very feasible category. Empirical testing showed that all test items were valid and showed high reliability (α = 0.959). The analysis of item difficulty levels varied, with a distribution of test items categorized as easy (12%), moderate (64%), and difficult (24%), while the item discrimination index showed that the majority of test items were in the very good category (64%). The results obtained indicate that the developed HOTS assessment instrument is feasible and can be used to stimulate and enhance students’ Higher Order Thinking Skills on the ecosystem topic